Model-based pain and function outcome trajectory types for patients undergoing knee arthroplasty: a secondary analysis from a randomized clinical trial. Issue 6 (June 2019) - Dumenci, L.; Perera, R.A.; Keefe, F.J.; Ang, D.C.; Slover, J.; Jensen, M.P.; Riddle, D.L.
Summary: Objective: Knee arthroplasty (KA) is an effective surgical procedure. However, clinical studies suggest that a considerable number of patients continue to experience substantial pain and functional loss following surgical recovery. We aimed to estimate pain and function outcome trajectory types for persons undergoing KA, and to determine the relationship between pain and function trajectory types, and pre-surgery predictors of trajectory types. Design: Participants were 384 patients who took part in the KA Skills Training randomized clinical trial. Pain and function were assessed at 2-week pre- and 2-, 6-, and 12-months post-surgery. Piecewise latent class growth models were used to estimate pain and function trajectories. Pre-surgery variables were used to predict trajectory types. Results: There was strong evidence for two trajectory types, labeled as good and poor, for both Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain and Function scores. Model estimated rates of the poor trajectory type were 18% for pain and function. Dumenci's latent kappa between pain and function trajectory types was 0.71 (95% CI: 0.61–0.80). Pain catastrophizing and number of painful body regions were significant predictors of poor pain and function outcomes. Outcome-specific predictors included low income for poor pain and baseline pain and younger age for poor function. Conclusions: Among adults undergoing KA, approximately one-fifth continue to have persistent pain, poor function, or both. Although the poor pain and function trajectory types tend to go together within persons, a significant number experience either poor pain or function but not both, suggesting heterogeneity among persons who do not fully benefit from KA.